HMPA (Hukum Materiil Peradilan Agama) Tentang Ahli Waris Pengganti : Tinjauan Ontologi, Epistimologi, Dan Aksiologi Hukum Islam - Sharfina Permata Noor, Erla; Jalaluddin, Jalaluddin; Azhari, Fathurrahman; Hamdi, Fahmi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abtrack This paper examines the concept of substitutional heir (plaatsvervulling) in Islamic inheritance law from the perspectives of ontology, epistemology, and axiology. The concept of substitutional heir regulates the inheritance mechanism when the primary heir (biological child) has passed away before the testator (parent). Differences in interpretation among Islamic legal scholars regarding this concept can affect the final outcome of inheritance distribution, especially in cases involving complex family structures. This paper aims to unify perspectives and develop a comprehensive guideline on the application of the substitutional heir concept. From the ontological aspect, the paper explores the essence and philosophical foundation of this concept within Islamic teachings. Epistemologically, the paper examines the sources and interpretive methods used. From the axiological perspective, the paper evaluates the values and objectives to be achieved through the implementation of this concept in realizing justice, utility, and general welfare in the distribution of inheritance according to Islamic law. Keywords: Substitutional heir (plaatsvervulling), Islamic inheritance law, Ontology of Islamic law, Epistemology of Islamic law, Axiology of Islamic law. Abstrak Makalah ini mengkaji konsep ahli waris pengganti (plaatsvervulling) dalam hukum kewarisan Islam dari perspektif ontologi, epistemologi, dan aksiologi. Konsep ahli waris pengganti mengatur mekanisme pewarisan ketika ahli waris utama (anak kandung) telah meninggal lebih dulu daripada pewaris (orang tua). Perbedaan interpretasi di kalangan ahli hukum Islam terkait konsep ini dapat mempengaruhi hasil akhir pembagian harta warisan, khususnya dalam kasus yang melibatkan struktur keluarga kompleks. Makalah ini bertujuan untuk menyatukan pandangan dan menyusun pedoman komprehensif mengenai penerapan konsep ahli waris pengganti. Dari sisi ontologi, dibahas hakikat dan landasan filosofis konsep ini dalam ajaran Islam. Secara epistemologi, dikaji sumber dan metode interpretasi yang digunakan. Dari sisi aksiologi, dinilai nilai-nilai dan tujuan yang ingin dicapai melalui implementasi konsep ini dalam mewujudkan keadilan, kemanfaatan, dan kemaslahatan umum dalam pembagian harta warisan. Kata Kunci : Ahli waris pengganti, Hukum kewarisan Islam, Ontologi hukum Islam, Epistemologi hukum Islam, Aksiologi hukum Islam